A COMPARISON BETWEEN X-RAY AND CARBON ION IRRADIATION IN HUMAN NEURAL STEM CELLS. Issue 1 (11th December 2018) - Morini, J; Babini, G; Barbieri, S; Baiocco, G; Ciocca, M; Ivaldi, G B; Liotta, M; Molinelli, S; Tabarelli de Fatis, P; Ottolenghi, A
Abstract: Glioblastoma multiforme (GBM) is characterized by a poor prognosis and a median survival of ~12–18 months. GBM is usually managed by neurosurgery followed by both chemotherapy and radiotherapy. Since GBM develops resistance to conventional therapies, treatment with C-ions is promising to completely eradicate the tumoural mass. During cranial irradiation, exposure of healthy tissues is inevitable. Because of the presence of neural stem cells, a deep investigation on the effects of C-ion irradiation with respect to X-ray induced damage is mandatory to allow a better definition of treatments. In this work, the comparison of X-rays and C-ion irradiation-induced effects on human neural stem cell, focusing on multiple endpoints, such as cell viability, cytokine secretion and spheroid formation is presented. Results show different temporal and dose responses of human neural stem cells to the different radiation qualities, suggesting different underpinning mechanisms of radiation-induced damages.